Linking Engineering and the Humanities: new ways for professional development. - Trujillo-Aguilera, F. David; Blázquez-Parra, Elidia Beatriz; Ladrón-de-Guevara-López, Isidro (My University, 2023)
The European Higher Education Area (EHEA), the changes in the regulations that structure the Spanish University System and the new organization of degree programs, have brought about a new concept of university in which it is especially necessary to optimize resources and control their return to society. As a consequence of this vision, the universities must guarantee in their actions the fulfilment of the objectives associated with the courses they teach, also seeking their continuous improvement. University education represents a significant investment of public resources, the ultimate aim of which is to create professionals who respond to the labor demands of the socio-economic fabric of their environment. In accordance with these premises, the University of Malaga is developing a 1st Employability Plan, which constitutes a guiding instrument that includes the measures and actions to be implemented to improve the visibility of our graduates in the labor market. The School of Telecommunications Engineering (ETSIT) participates in this initiative through a proposal that aims to encourage students to change their vision and see the importance of the relationship between Technology and Humanities.
Keywords: Enseñanza superior - Aspectos sociales; Ciencia y humanidades; Interdisciplinariedad en la enseñanza; EEES; Habilidades blandas; Plan de empleabilidad; Humanidades; Tecnología; Sociedad; Ingeniería